Historical earthquake records in the Weihe Basin, central China and new insights for geothermal genesis - Zhou, Bing; Zhang, Yancheng; Kuang, Jian (Frontiers in Earth Science, 2024)
The Weihe Basin, located in central China, stands out for its significant earthquake activity while concurrently harboring promising geothermal reservoirs. The potential association between these two geological occurrences and the underlying mechanisms remain enigmatic. Here, we compile a catalog of historic earthquakes, total strain data, data related to crustal mantle structure, surface heat flow data, and heat production data of the rocks in the Weihe Basin. Our aim is to unveil the intricate interplay among the occurrence of earthquakes, tectonic activity, and the genesis of geothermal resources. Our findings reveal that earthquake activity in the Weihe Basin is regulated by the responses of faults or fractures intricately influenced by regional tectonics. These tectonic processes are responsible for the formation of favorable geothermal resources beneath the basin. We propose there is a weak zone beneath the basin, which is controlled by a combination of tectonic processes and the flow of the asthenosphere. We finally establish a comprehensive model to visualize the genesis of the occurrence of earthquakes and the formation of geothermal resources. These results have important guiding significance for future research endeavors in the realms of both geothermal exploration and earthquake investigations within the Weihe Basin.